Effects of the BPAL Regimen On Hematological Parameters In Patients With Multidrug-Resistant Tuberculosis - Dwi Retnoningrum; Sustika Novianita Assan; Villa Sekar Cita; Ardhea Jaludamascena (Diponegoro International Medical Journal, 2026)
Background: BPaL is a new oral drug combination consisting of Bedaquiline (B), Pretomanid (Pa) and Linezolid (L) for multi-drug resistance tuberculosis. In Indonesia BPaL has been officially launched by the government as a therapeutic regimen for multidrug resistant tuberculosis patients since August 2023. One of the drugs in this regimen has the side effect of anemia. Until now, there are still no references explaining the effect of BPaL on the hematological profile.Objective: To determine the differences in the hematological profile of multidrug resistance tuberculosis patients before receiving the multi drug resistance regimen BPaL anti-tuberculosis drug regimen and while receiving the multi drug resistance regimen BPaL anti-tuberculosis drug regimen.Methods: This research was a retrospective observational analytical study with a retrospective cohort design involving patients with multidrug-resistant tuberculosis in Kariadi Hospital based on medical records. The difference test used the paired T-test and the Wilcoxon test.Results: 40 subjects were recruited, there were significant differences in hemoglobin level (p=0.003), hematocrit (p=0.002), red blood cells count (p=<0.001), white blood cells count (p=0.004), platelet count (p=<0.001) and RDW (p=<0.001) before therapy with the BPaL regimen and during therapy with the BPaL regimen.Conclusion: There are significant differences in the hematological profile of multidrug resistant patients, before treatment with the BPaL regimen and while receiving the BPaL regimen.